Efferocytosis of apoptotic human papillomavirus‐positive cervical cancer cells by human primary fibroblasts. (20th April 2016) - Hermetet, François; Jacquin, Elise; Launay, Sophie; Gaiffe, Emilie; Couturier, Mélanie; Hirchaud, Fabienne; Sandoz, Patrick; Prétet, Jean‐Luc; Mougin, Christiane
Research article: The underlying mechanisms of fibroblast‐mediated efferocytosis are not well understood. Here we demonstrate that non‐professional phagocytes engulf subcellular fragments rather than dying whole cells requiring the recognition of phosphatidylserine (PS) by receptor Brain‐specific Angiogenesis Inhibitor 1 (BAI1) and actin cytoskeleton remodelling. Lysosomal‐associated membrane protein‐1 (LAMP‐1) and microtubule‐associated protein 1 light chain 3 (LC3) colocalise on apoptotic cell‐containing phagosomes. Abstract : Background information: Efficient clearance of apoptotic cells, named efferocytosis, is a fundamental physiological process for tissue development and homeostasis. The contribution of non‐professional phagocytes like fibroblasts to efferocytosis has been established, although the underlying mechanisms are not well understood. We recently demonstrated that horizontal DNA transfer can occur through the uptake of apoptotic human papillomavirus‐positive cancer cells by human primary fibroblasts leading to their transformation. The aim of this present study was to analyse the cellular and molecular mechanisms that drive the phagocytic activity of human primary fibroblasts in the context of apoptotic cervical cancer cell removal. Results: Here we provide evidence that human primary fibroblasts engulf late more efficiently than early apoptotic cells, but their phagocytic ability remains limited compared to professional phagocytes such as human monocyte‐derived macrophages. The engulfment occurs in a time‐, temperature‐ and calcium‐dependent manner. Remodelling of actin‐fibers contributes to the biogenesis of apoptotic cell containing macroendocytic vacuoles. Both morphological analyses and pharmacological approaches confirmed the involvement of actin‐driven phagocytosis and likely macropinocytotic mechanisms in apoptotic target internalization. The uptake of apoptotic cells requires phosphatidylserine recognition, which is mainly mediated by phosphatidylserine‐receptor brain‐specific angiogenesis inhibitor 1. Confocal microscopy analyses with organelle‐specific markers revealed that internalised apoptotic material traffics into late phagolysosomes and specific features of microtubule‐associated protein 1 light chain 3‐associated phagocytosis were observed. Conclusions: Our in vitro data show that fibroblasts contribute to apoptotic tumour cell removal by phagocytosis and likely macropinocytotic mechanisms. Efferocytosis by fibroblasts involves phosphatidylserine receptor brain‐specific angiogenesis inhibitor 1, which participates in subsequent uptake orchestration via actin cytoskeleton remodelling. Significance: Our results highlight the cellular and molecular mechanisms of fibroblast‐mediated clearance of apoptotic tumour cells. Consequences regarding alternative mechanism of carcinogenesis or tumour progression should be addressed.